Editorial (2020)
The Universidad Santo Tomás, Seccional Tunja, presents the journal Principia Iuris No. 34, in which topics of vital importance for the legal progress are developed, conceived from the social projection, and with axiological and epistemological bases that contribute to the solution of the different problems of disciplinary and interdisciplinary investigation. The research in this edition is the development of topics that cover a great content of social and legal problems, both in a national and international context. On this occasion, the Principia Iuris Journal, Series 34, presents articles that investigate and delve into important epistemological problems, which are highly topical in the area of law. Therefore, the reader will find a very interesting repertoire of legal and biojuridical issues in this issue. The permanent and inexhaustible effort of the jurists and participants of this edition is highlighted by us, and with its greatness, by the whole science of law.